Reverse retrospective motion correction. Issue 6 (3rd July 2015) - Zahneisen, Benjamin; Keating, Brian; Singh, Aditya; Herbst, Michael; Ernst, Thomas
Abstract : Purpose: One potential barrier for using prospective motion correction (PMC) in the clinic is the unpredictable nature of a scan because of the direct interference with the imaging sequence. We demonstrate that a second set of "de‐corrected" images can be reconstructed from a scan with PMC that show how images would have appeared without PMC enabled. Theory and Methods: For three‐dimensional scans, the effects of PMC can be undone by performing a retrospective reconstruction based on the inverse of the transformation matrix used for real time gradient feedback. Retrospective reconstruction is performed using a generalized SENSE approach with continuous head motion monitored using a single‐marker optical camera system. Results: Reverse retrospective reconstruction is demonstrated for phantom and in vivo scans using an magnetization‐prepared rapid gradient echo (MPRAGE) sequence including parallel and Partial Fourier acceleration. Conclusion: Reverse retrospective reconstruction can almost perfectly undo the effects of prospective feedback, and thereby provide a second image data set with the effects of motion correction removed. In case of correct feedback, one can directly compare the quality of the corrected with that of the uncorrected scan. Additionally, because erroneous feedback during PMC may introduce artifacts, it is possible to eliminate artifacts in a corrupted scan by reversing the false gradient updates. Magn Reson Med 75:2341–2349, 2016. © 2015 Wiley Periodicals, Inc.